An Islamic wealth management investment appraisal of oil tankers - Abdullah, Adam; Hassan, Rusni; Kassim, Salina (EconJournals, 2017)
The purpose of this research is to develop an Islamic wealth management investment appraisal of the performance of tankers as a primary segment within international shipping and an important component of the oil and energy markets. Shipping is a strong growth industry with about 84% of global trade carried by the international shipping industry. The problem is that many Islamic wealth management institutions and investors have minimal exposure to investment in international shipping. However, shipping is a highly capital intensive industry and currently 75% of ship lending has been conducted by European banks and financed on a conventional basis. Post financial crisis, ship owners, ship lenders and shipyards have all been exposed to the impact of over-levered balance sheets and debt finance. Our objectives are to evaluate the risks and returns of shipping under the framework of Islamic equity finance, and to analyze the performance of investing in tankers over the long term, in order to appeal to private and institutional clients. Accordingly, our methodology adopts an investment analysis of a full population of historical data over a period of 20 years, to evaluate performance involving a maritime return on investment, internal rate of return, net yield and standard deviation measures of risk and return. Our findings reveal that whilst earnings are volatile in comparison to capital market financial products, unlevered, tax-free returns on tanker investments out-perform financial and other real assets. The significance is that Islamic equity finance, rather than debt at the time-value-of-money, should enhance investment in the tanker sector.